Effect of Electroacupuncture at Changqiang on Expression of PSD-95 and CREB in Hippocampus CA1 Region of FMRI Knockout Mice - Lanfang CHEN; Xuejun ZHANG; Dong LIN; Shugui LAI; Qianru HUANG; Qiang WU (康复学报)
Objective:To explore the effect of electroacupuncture at Changqiang on expression of postsynaptic density protein-95 (PSD-95) and cAMP-response element binding protein (CREB) in hippocampus CA1 region of FMRI knockout mice.Methods:Thirty FMRI knockout mices at 28 days old were randomly divided into Changqiang group (n=10), non-acupoint group (n=10) and model group (n=10). In Changqiang group, the mices were treated by acupuncturing Changqiang, then received electroacupuncture stimulus for 20 minutes (continuous wave), and the treatment was given once daily for six times per week and lasted for two weeks. The same electroacupuncture manipulation as Changqiang group was used in non-acupoint group, where non-acupoint in the right rib was selected. The model group was reared under the same conditions without any intervention. The learning and memory ability of rats in each group were observed by using Morris water maze, and the PSD-95 and CREB protein expression in hippocampus CA1 region were detected by immunohistochemical techniques.Results:Compared with the model group and the non-acupoint group, the escape latency in Changqiang group was decreased significantly (P<0.05), the ratio of swimming distance in platform quadrant to total swimming distance was increased (P<0.05), and the PSD-95 and CREB protein expression in hippocampus CA1 region were increased respectively (P<0.05).Conclusion:Electroacupuncture at Changqiang can improve the learning and memory ability in FMR1 knockout mice, and the mechanism may be related to the regulation of PSD-95 and CREB protein expression in hippocampus CA1 region.